PEMBERDAYAAN GURU SEKOLAH DASAR DALAM IMPLEMENTASI LITERASI BUDAYA DAN KEWARGAAN BERORIENTASI KEARIFAN LOKAL - Beti Istanti Suwandayani; Yohana Puspitasari Wardoyo; Ferranza Auliya Tiza; Nanda Melinia Safitri; Khofifah Pawaranca Hadi; Alfinda Handayani; Uci Nurul Hidayati (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
The development of the global era affects the development of local wisdom in the region. This is reinforced by the declining literacy data in Indonesia. The purpose of this activity is to provide assistance to teachers as agents of change for the superior generation. Participants in this activity were elementary school teachers at SD Muhamamdiyah 8 Dau, Malang Regency. The methods used include lectures, discussions, simulations and mentoring. The result of this activity is an increase in the quality of understanding cultural literacy and citizenship. Increasing the use of technology in developing learning media and implementing cultural literacy and citizenship through learning by producing products in the form of posters and reference books for students. The book is packaged in two versions, namely an e-book version that students can read at home, while the hard book version that students read when carrying out face-to-face learning is limited at school. From this mentoring activity, the teacher participants at SD Muhammadiyah did a very good process. Starting from recognizing cultural literacy and citizenship, digging data and producing findings, processing data to pouring ideas into local wisdom products.